The bank lending channel in a simple macro model: How to extend the Taylor Rule? - Peter Spahn (Research On Money in the Economy (ROME), 2014)
The growth and deepening of financial markets entailed the expectation that the bank lending channel of monetary policy transmission would lose its importance. The paper explains why, on the contrary, the banking sector has become a major locus of origination and amplification of macro-financial shocks. Mutual feedback mechanisms between the financial and the real sector are analysed and simulated by using a simple standard macro model with an integrated banking system. A comparison of the efficiency of various Taylor Rule extensions explores whether monetary stabilisation can be improved by additional interest rate reactions to asset prices, bank lending, bank leverage or the spread between the loan and the policy rate.
Keywords: E1; E5; G2; 330; monetary policy transmission; credit market; leverage targeting; risk-taking channel; asset market shocks